Assessment of in vitro bioaccessibility of manganese in wheat flour by ICP-MS and on-line coupled with HPLC. (May 2016) - Erdemir, Umran Seven; Gucer, Seref
Abstract: In this study, in vitro simulated enzymatic digestion methods combined with n -octanol extraction, activated carbon adsorption, and chemical fractionation studies were applied to wheat flour samples to assess the bioaccessibility of manganese. Matrix characterization by macro chemical compositions of the samples and fractionation studies were evaluated in the context of enzymatic digestibility using also a new methodological approach to assess the accuracy of in vitro methods. Manganese levels in fractions and digests were determined by inductively coupled plasma-mass spectrometry (ICP-MS). Additionally, water fractions were analyzed by reversed-phase high performance liquid chromatography coupled on-line to ICP-MS for rapid screening of the free manganese contents. The limits of detection achieved for this hyphenated technique were 3.6 μg L −1 for manganese. The bioaccessible levels of manganese in the samples were found to be in the range from 64 to 67% of the total amount. The manganese content in water fractions achieved by the on-line hyphenated technique was found compatible with respect to bioaccessibility of manganese. Furthermore, recommended daily intake values together with the bioaccessible levels were used for the risk assessment studies. Depending on the recommended dietary allowance of manganese for adults, 100 g of flour may supply 14–24% of daily manganese intake. Highlights: Bioaccessibility of manganese was assessed by in vitro methods in wheat flour. The bioaccessible levels of manganese were found to be in the range from 64 to 67%. Chemical fractionation studies indicate the importance of protein-bound manganese. Water fractions were analyzed by reversed-phase HPLC coupled on-line to ICP-MS. On-line hyphenated technique was found compatible with respect to in vitro methods.